ANALISIS PENGARUH IDENTITAS MERK DAN CO-BRANDING MUSISI LOKAL TERHADAP LOYALITAS PELANGGAN DI BORSUMY HERITAGE - Sofari Fuqoha, M Ilham; Surayya Ulfa, Nurist; Luqman, Yanuar (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The growth of the hotel industry is growing rapidly both on a global and national scale. The hospitality industry includes hotels and food service providers such as coffee shops, cafes and bars. In 2022, cafes in Indonesia will show a value of 1.9 million US Dollars or 30.2 trillion Rupiah. The development of this industry is also in line with the growth of Indonesian society. The more cafe choices there are, the more competition between cafes increases. Cafes compete to bring in loyal customers through a strong brand identity and co-branding with local musicians, as is done by Borsumy Heritage. Therefore, further research is needed to maintain loyal customers. This research aims to describe the influence of cafe brand identity and perceptions of co-branding with local musicians on customer loyalty in cafes. This research is an explanatory quantitative research with a non-probability sampling technique involving 100 respondents. The research results show that brand identity has no partial effect on cafe customer loyalty, co-branding with local musicians has a partial effect on cafe customer loyalty. Meanwhile, brand identity and co-branding with local musicians simultaneously influence cafe customer loyalty.